Reproducibility of cardiorespiratory and cellular responses to steady state exercise in hypoxia and preloaded cycling time trial performance reliability in normoxia and acute hypoxia - Lee,Ben J; Thake,Charles D (PeerJ PrePrints, 2015)
Background. The purpose of this study was to assess the reproducibility of cardiorespiratory and cellular (monocyte heat shock protein 70; mHSP70) responses to a fixed load hypoxic stress test (HST) and the reliability of a pre-loaded 16.1km cycling time trial (pTT) conducted under both normoxic and hypoxic conditions. Methods. Eighteen participants (age, 22 ± 4 years; height, 1.77 ± 0.04 meters; body mass, 76.8 kg; estimated body fat and VO2peak = 3.50 ± 0.60 L.min-1) were divided into three groups. Reliability of responses (HR, SPO2, VO2, VCO2, VE and RER) to the HST (FIO2 0.14; 15 minutes rest, 60 minutes cycling at 50% normoxic VO2peak) was assessed across 3 repeat trials (HST 1, 2 and 3, n = 6); mHSP70 was measured via flow cytometry before and after each HST (n = 5); resting HSP was also quantified on 4 separate occasions (n=5). Reliability of the pTT (15 min rest, 40 minutes cycling at 50% normoxic VO2peak) was assessed across 3 repeat normoxic (N; FIO2 ≈ 0.21; n=6) and 3 repeat hypoxic (FIO2 ≈ 0.14; n = 6) trials. All exercise trials were undertaken at the same time of day, following exercise and dietary controls, 7 days apart. Results. Intra-class correlation coefficients (ICC’s) for mean and peak HR, SpO2, VE , VO2 , VCO2 and BLa within each trial were improved from HST1 to HST2 (mean data: 0.99, 0.95, 0.75, 0.62, 0.70, 0.90; peak data: 0.98, 0.96, 0.64, 0.69, 0.74, 0.75) to HST2 and HST3 (ICC = 0.99, 0.97, 0.82, 0.85, 0.87 and 0.96 respectively). mHSP70 was a reproducible at rest without (ICC > 0.95) and with HSTs conducted in the previous 7 days (ICC > 0.95), with no difference in pre to post increases in mHSP70 observed between tests. The reliability for time to pTT completion was improved following one trial, and the CV (test 2 vs. 3) was similar under normoxic (CV = 0.62) and hypoxic conditions (CV = 0.63). Conclusion. Cardiorespiratory and cellular responses to the HST were reproducible and the pTT performance time reliable in both N and H. Since the reproducibility of the measurements in HST trials and reliability of pTT improved between the second and third trials one familiarization visit is recommended prior to employing these protocols in future studies.
Keywords: Hypoxia; Exercise; heat shock protein 70; time trial performance; reproducibility